The perspective of professionals vis-à-vis minors: fundamental for child welfare (Praxis Educativa, 2021)
The study starts from the understanding of the childhood as a vulnerable period. Thus, the way that the different professionals take action during that stage proves to be an essential aspect in order to boost their wellbeing. In this sense, this article examines two theoretical perspectives of vulnerable and unprotected minors, by making a distinction between child protection and child welfare. From now on, we state a case study developed in a Basque Country municipality. The focus of this study is the work conducted by the municipality’s social committee, as well as the committee’s social workers’ perspective of children and teenagers. For that purpose, we opted for a qualitative and participatory methodology, focused on document content analysis and semi-structured interviews. Finally, we conclude that the municipal social workers` perspective consists on a child welfare-based approach.
Keywords: minors; children; vulnerability; education